2015
DOI: 10.1332/030557314x13917703359707
|View full text |Cite
|
Sign up to set email alerts
|

Public–private partnerships, management capacity and public service efficiency

Abstract: By working with business, public organisations are assumed to benefit from: a more contestable procurement process; access to private sector entrepreneurialism and the realisation of previously untapped scale economies. Nevertheless, realisation of these benefits may be contingent upon an expansion of management capacity to cope with vastly increased transaction costs. We examine the relationship between a commitment to public-private partnerships, management capacity and the productive efficiency of a set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 36 publications
(42 reference statements)
1
53
0
4
Order By: Relevance
“…Otherwise, results in the study of Doumpos and Cohen () did not follow a linear pattern (the coefficient was negative for small municipalities and positive for medium and large municipalities). Finally, Andrews and Entwistle () did not find population size related to efficiency. Age distribution of the population (10 papers)The different age distribution of the population can have an impact on the different needs that local governments have to satisfy. Mainly, two variables are included: share of young people (18 years old or below) and share of retired people (over 65 years old).…”
Section: Environmental Variablesmentioning
confidence: 91%
See 1 more Smart Citation
“…Otherwise, results in the study of Doumpos and Cohen () did not follow a linear pattern (the coefficient was negative for small municipalities and positive for medium and large municipalities). Finally, Andrews and Entwistle () did not find population size related to efficiency. Age distribution of the population (10 papers)The different age distribution of the population can have an impact on the different needs that local governments have to satisfy. Mainly, two variables are included: share of young people (18 years old or below) and share of retired people (over 65 years old).…”
Section: Environmental Variablesmentioning
confidence: 91%
“…Otherwise, some studies concluded that the share of retired people has no statistical significance . Finally, the study of Radulovic and Dragutinović () included an “ageing index”, that is, a ratio between the number of people over 65 and the number of people under 18, while Andrews and Entwistle () included the age diversity. Only Radulovic and Dragutinović () found significant results, showing a negative relation between the age index ratio and efficiency. Education level (17 papers)Education level includes primary, secondary and tertiary education.…”
Section: Environmental Variablesmentioning
confidence: 99%
“…8 Similarly, Lampe et al (2015) and Asatryan and De Witte (2015) measured total government expenditures net of transfers from the central government to municipalities arguing that municipalities have no discretion to make decisions on their use. 7 Kalseth and Rattsø (1995), Kerstens (1996a, 1996b), Prieto and Zofio (2001), Fernandes (2003, 2006), Coffé and Geys (2005), Afonso and Fernandes (2008), Balaguer-Coll et al (2010b), Kutlar and Bakirci (2012), Nakazawa (2013Nakazawa ( , 2014, Ashworth et al (2014), Pevcin (2014aPevcin ( , 2014b, Mahabir (2014), Yusfany (2015), Andrews and Entwistle (2015). 8 Sung (2007) I.…”
Section: Financial Expendituresmentioning
confidence: 99%
“…Total expenditures Kalseth and Rattsø (1995), Kerstens (1996a, 1996b), Prieto and Zofio (2001), Afonso and Fernandes (2003), Coffé and Geys (2005), Afonso and Fernandes (2006), Sung (2007), Afonso and Fernandes (2008), Seol et al (2008), Nijkamp andSuzuki (2009), Balaguer-Coll et al (2010b), Kutlar and Bakirci (2012), Nakazawa (2013Nakazawa ( , 2014, Ashworth et al (2014), Pevcin (2014aPevcin ( , 2014b, Mahabir (2014), Yusfany (2015), Andrews and Entwistle (2015), Asatryan and De Witte (2015), Lampe et al (2015), Cordero et al (2016)…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation